Attitudes and graduation in play store's review about Mobile Legend: Bang-Bang - Rahmaditya Khadifa Abdul Rozzaq Wijaya; Ratini Setyowati; Winarti Winarti; Aris Hidayatulloh; Abdul Ayiz (LP2M Universitas Sarjanawiyata Tamansiswa, 2024)
This research is descriptive qualitative research. This research aims to describe the Attitude System and Graduation System that appear in reviews of Mobile Legend on the Play Store platform. The data in this research are utterances containing the Attitude System and Graduation System. The data source for this research was taken from reviews on the Play Store's Review of Mobile Legend: Bang-bang. Next, the data collection technique uses content analysis. Then, data analysis techniques use domain analysis, taxonomic analysis and componential analysis. In this research, researchers found 157 appreciation data, 115 judgment data, and 99 affect data. In conclusion, from all the data, appreciation data is the highest data. This is because reviewers evaluate the mechanical elements in the game more. For example, matchmaking, bugs / lag, reward system, season changes, and so on.